Color variations based on strong-interference effects in oxygen-defective tetragonal ZrO2–x films in nanometer thickness produced by oxidation of zirconium metal foil. (October 2021) - Himeno, Yuta; Matsuda, Mitsuhiro; Shida, Kenji; Matsuda, Motohide
Abstract: A strong-interference film that absorbs visible light by using oxygen-deficient ZrO2 – x was produced by heat treatment of Zr metal foil under a low partial pressure of oxygen. The oxygen-defective tetragonal ZrO2 – x film contained nanocrystallites several nanometers in size and its thickness ( t ) increased from 30 to 140 nm on increasing the holding time during heat treatment. The color of the sample changed depending on the thickness of the oxygen-deficient ZrO2 – x film from gold ( t = 30 nm) through blue ( t = 75 nm) to black ( t = 140 nm). Thick ZrO2 – x films ( t ≧ 140 nm) absorbed all visible light, leading to the observed black color, whereas in thinner films ( t < 140 nm), strong interference resulted in changes in the sample color, for example, from gold to blue. Graphical abstract: Fig. The appearances of a sample (a) before heating and after heating the Zr metal foil at 1273 K for (b) 1.8ks, (c) 3.6 ks, (d) 5.4 ks under PO2 = 1.0 × 10-10 atm. Image, graphical abstract